Combustion characteristics of direct-injection spark-ignition engine fuelled with producer gas - Hagos, F.Y. (2013)
This study presents the combustion characteristics ofanimitatedlow caloric value syngas (producer gas)fuelled in 4-stoke, single cylinder, Direct-injection (DI) Spark-ignition (SI) engine. The gas has a composition of 19.2 H2, 29.6 CO, 5.3 CH4, 5.4 CO2 and 40.5 N2. This resemblesa typical product of wood biomass gasification. The engine was operated at 75 throttle valve opening. Peak combustion pressure was observed at the top dead center (TDC) in all operation conditions. The maximum rate of pressure rise was observed in the range of 13.5 to 18.5Â°BTDC (Before Top Dead Center) for all operation conditions. This is attributed to the advanced ignition angle for the maximum brake torque, prompting high heat loss through the walls of the combustion chamber. The mass fraction burn (MFB) curves exhibit a double-Wiebe function at all engine speeds. Possible explanations to this may be wall heat loss, flame quenching and double flame fronts due to different combustion behaviors of hydrogen and other combustible gases. The difference in laminar flame speed and auto-ignition temperature of hydrogen and the other combustible gases prompted a delay period between the quenching of the flame front of hydrogen and auto-ignition of after-burning gases. The results also show that combustion of a low calorific value fuels in a direct-injection engine is possible only under ultra-lean operating condition. This is mainly attributed to the failure of the injection system to deliver the required amount of fuel in a very short injection duration to achieve richer mixtures. Â© Sila Science.